STUDYING QUALITY OF LIFE IN DOMESTIC PEDIATRICS: RESULTS, GOALS AND STUDY PROSPECTS - A.A. Baranov; V.Yu. Al'bitsky; I.V. Vinyarskaya; S.A. Valiulina ("Paediatrician" Publishers LLC, 2007)
In the recent years, both clinical and social pediatrics have been intensively studying quality of life of children. The article discusses the main trends of quality of life indicators study. In social pediatrics, they are oriented at studying quality of life of different segments of children; development of quality of life standards depending on the gender, age, health; regional peculiarities of quality of life; study of the indicator in disabled children, children from different social groups, and at the efficiency evaluation of preventive measures in pediatrics. In the clinical studies, the prevalent attention goes to the estimation of how the disease impacts quality of life of children, how efficient the treatment is, and focuses on pharmaeconomics. The article lists the results for the major trends and the significant tasks for the nearest future. Key words: quality of life, medico-social study, clinical study.